The Impact of Organizational Readiness on Financial and Project Performance from the Employee's Perspective: A Case Study - Gumilang, Zahwa Fitria; Prihartono, Budhi (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2025)
The COVID-19 pandemic forced non-essential sectors to limit operations, leading to financial decline. Organizational readiness to adopt digital technology has become critical for firms' survival. However, limited empirical research has explored the correlation between organizational readiness, financial performance, and project performance. This study aims to address this gap by examining these relationships. Using a quantitative approach, this study employed non-probability purposive sampling, collecting 85 data points between December 27, 2021, and January 27, 2022. A total of 30 indicators were used to measure five research constructs, and the data were analyzed using the PLS-SEM method with SmartPLS software. The findings indicate that organizational readiness positively influences project performance through the mediating effect of organizational capabilities, specifically dynamic capabilities and project management capabilities. Both dynamic capabilities and project management capabilities positively affect project performance. Additionally, the study reveals a positive correlation between project performance and financial performance. However, dynamic capabilities do not significantly impact project management capabilities. This study suggests that top management should optimize the utilization of existing assets, enhance technical capabilities, align resources with strategic objectives, foster innovation, secure organizational support, cultivate an innovative work environment, and maintain a clear business vision.